The External Factors that Influence Students’ Motivation in Studying English - Ingriyani Y Rawung (Sintuwu Maroso Journal of English Teaching, 2016)
This research is conducted to identify external factors that influenced students’ motivation in studying English. Th is research was a descriptive qualitative. The subjects of research was the first grade students of SMP Negeri 3 Poso. The datagathered were interpreted under the theory of mot ivat ion. The findings show that: 1) The external factors were fear of punishment, rewards and praises, teacher’s role, parent’s role, and environmental conditions, 2) The student’s low motivationswere caused by parent’s role, teacher’s role and environment conditions, and 3) The most influential external factors for student’s high motivation were rewards andpraises, and fear of punishment.Keywords: external factor, students motivation